Human challenge trials for vaccines against COVID-19 - Smith, Peter (Henry Stewart Talks, 2020)
Study design of human challenge trials and comparison with classical clinical trials, Previous vaccines tested in human challenge trials, How human challenge trials accelerate vaccine development, Drawbacks, limitations, and potential ethical issues, Possible COVID-19 vaccine candidates for human challenge trials